Reported autism diagnosis is associated with psychotic-like symptoms in the Adolescent Brain Cognitive Development cohort. - Jutla, Amandeep; Donohue, Meghan Rose; Veenstra-VanderWeele, Jeremy; Foss-Feig, Jennifer H. (European Child & Adolescent Psychiatry, 2022)
Although the schizophrenia (SCZ) rate is increased in autism spectrum disorder (ASD), it is difficult to identify which ASD youth will develop psychosis. We explored the relationship between ASD and emerging psychotic-like experiences (PLS) in a sample of 9127 youth aged 9–11 from the Adolescent Brain Cognitive Development (ABCD) cohort. We predicted that parent-reported ASD would be associated with PLS severity, and that ASD youth with PLS (ASD+/PLS+) would differ from ASD youth without PLS (ASD+/PLS−) and youth with PLS but not ASD (ASD−/PLS+) in cognitive function. We fit regression models that included parent-reported ASD, family history of psychosis, lifetime trauma, executive function, processing speed, working memory, age, sex, race, ethnicity, and income-to-needs ratio as predictors of Prodromal Questionnaire-Brief Child (PQ-BC) distress score, a continuous index of PLS severity. We assessed cognitive differences using regression models with ASD/PLS status and relevant covariates as predictors of NIH Toolbox measures. ASD increased raw PQ-BC distress scores by 2.47 points (95% CI 1.33–3.61), an effect at least as large as Black race (1.27 points, 95% CI 0.75–1.78), family history of psychosis (1.05 points, 95% CI 0.56–1.54), and Latinx ethnicity (0.99 points, 95% CI 0.53–1.45. We did not identify differences in cognition for ASD+/PLS+ youth relative to other groups. Our finding of association between ASD and PLS in youth is consistent with previous literature and adds new information in suggesting that ASD may be a strong risk factor for PLS even compared to established SCZ risk factors.